Evaluation of Empiric Antibiotic Therapy Toward Clinical Outcome in Children Patients with Bacterial Meningitis in Dr. Sardjito General Hospital Yogyakarta 2010-2015 - Wihda Yanuar; Ika Puspita Sari; Titik Nuryastuti (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Cases of bacterial meningitis in Indonesia reach 158/100,000. Bacterial meningitis attacks children less than 2 years old. Patients with bacterial meningitis who survive are at risk for complications such as brain damage. Therefore, patients with bacterial meningitis, especially in children, need to get optimal therapy. This study aims to determine the pattern of empirical antibiotic use on clinical outcome of pediatric patients with bacterial meningitis in the inpatient ward of Sardjito General Hospital. The study was conducted in an observational descriptive design by collecting data retrospectively on the medical records of patients who met the inclusion criteria. There were 25 patients who met the inclusion criteria. The results showed that 26% use of empiric antibiotics was in accordance with the guidelines for the treatment of bacterial meningitis. Empiric therapy increased clinical outcomes of 40% patients.